2020
DOI: 10.1177/1179573519894955
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influencers, MicroRNA, and Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a complex neurological disorder characterized by an aberrant immune system that affects patients’ quality of life. Several environmental factors have previously been proposed to associate with MS pathophysiology, including vitamin D deficiency, Epstein-Barr virus (EBV) infection, and cigarette smoking. These factors may influence cellular molecularity, interfering with cellular proliferation, differentiation, and apoptosis. This review argues that small noncoding RNA named microRNA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 269 publications
(754 reference statements)
0
17
0
3
Order By: Relevance
“…Small noncoding microRNAs (miRNAs or miR) are an important class of molecules critically involved in modulating gene expression and are considered sensitive biomarkers and potential therapeutic targets for many diseases 8,9 . Notably, altered expression of various miRNAs (including, miR‐155 and miR‐21) have been detected in the peripheral blood, CSF and brain tissue of MS patients and in one of the most widely used animal model of MS, experimental autoimmune encephalomyelitis (EAE) 10,11 . It has been shown that different therapeutic approaches may modulate the expression and activity of specific miRNA and particularly of miR‐142‐3p 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Small noncoding microRNAs (miRNAs or miR) are an important class of molecules critically involved in modulating gene expression and are considered sensitive biomarkers and potential therapeutic targets for many diseases 8,9 . Notably, altered expression of various miRNAs (including, miR‐155 and miR‐21) have been detected in the peripheral blood, CSF and brain tissue of MS patients and in one of the most widely used animal model of MS, experimental autoimmune encephalomyelitis (EAE) 10,11 . It has been shown that different therapeutic approaches may modulate the expression and activity of specific miRNA and particularly of miR‐142‐3p 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…to show that the empirical distribution of the overlaps does not match with the expected hypergeometric distribution. First, we selected miRNAs dysregulated in multiple sclerosis, from Table 5 in [15] (see supporting information) and gene ontology (GO) annotations from Ensembl [23] version 100. Also we retrieved disease-to-gene associations from DisGeNET v7 [18], as well as pathway data from KEGG [11].…”
Section: Methodsmentioning
confidence: 99%
“…miR-17, miR-21, miR-320, and miR-150 exhibited different patterns across the compartments in MS patients with predominant upregulation in the CNS lesions and downregulation in the immune tissue [55,58,59]. Interestingly, It has been reported that miR-21 exhibit both pro-and anti-inflammatory functions.…”
Section: Mirna Dysregulation Multiple Sclerosismentioning
confidence: 99%